Actual design space methodology for high-performance switched reluctance machines design - Rocca, Roberto (2020)
In the design of modern, high-performance Switched Reluctance machines, designers are challenged to face highly restrictive sets of constraints and requirements, which frequently tend to clash with each other. As a result, chances to find a feasible solution to the design problem reduce dramatically, in case a solution is at all available. Traditional design approaches, i.e. heuristic and optimisation-based, proved not to cope effectively with this kind of design problem, mainly because of their inherent impossibility to consider the interactions between the ‘physics’ involved in the design from the very early stages. A possible solution is therefore to change the way high-performance designs are approached. To this end, this thesis proposes a new approach to the design of high-performance Switched Reluctance machines, that is based on the introduction of an analytical stage prior to the Finite Elements stage, where the ‘Actual Design Space’ (ADS) is determined, i.e. the ‘space wherein the final design can be found’. The process to determine the ADS begins by the rigorous count of the number of independent design variables. Subsequently, constraints and requirements are introduced one by one, in order to discard all of the unfeasible candidates. At the end of this process, the ADS is attained, whose main characteristic is to be populated only by feasible candidates. As it can be noted, this approach is inherently multiphysics, since thermal, mechanical and electromagnetic constraints are all handled together. Following from the way the ADS is determined, the designer can benefit from a good insight of the design problem and hence is in the position to: 1) ensure that the design problem is feasible (ADS non-empty), and 2) once the feasibility has been proved, select the most convenient strategy to finalise the design via Finite Elements. The design case study of a 5.5kW Switched Reluctance machine for a mild hybrid automotive drive train concludes this thesis with a practical implementation of the proposed ADS methodology, showing its effectiveness in coping with a restrictive set of constraints and requirements.